2011
DOI: 10.1021/bi1016777
|View full text |Cite
|
Sign up to set email alerts
|

A Hearing Loss-Associated myo1c Mutation (R156W) Decreases the Myosin Duty Ratio and Force Sensitivity

Abstract: Myo1c is a member of the myosin superfamily that has been proposed to function as the adaptation motor in vestibular and auditory hair cells. A recent study identified a myo1c point mutation (R156W) in a person with bilateral sensorineural hearing loss. This mutated residue is located at the start of the highly conserved switch-1 region, which is a crucial element for the binding of nucleotide. We characterized the key steps on the ATPase pathway at 37 °C using recombinant wild-type (myo1c 3IQ ) and mutant myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 54 publications
2
45
0
Order By: Relevance
“…Myo1b is suited to function as a tension-sensitive anchor, transforming from a low duty-ratio motor to a high duty ratio-motor with forces resisting its working stroke >0.5 pN. Moreover, the rate of actin translocation in the in vitro motility assay is similar for both myo1b (21) and myo1c (16) (when corrected for the differences in length of the light chain-binding domain). Given the similarity of their unloaded biochemical properties, one may have expected myo1c to share the force-sensing properties of myo1b (22,23).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Myo1b is suited to function as a tension-sensitive anchor, transforming from a low duty-ratio motor to a high duty ratio-motor with forces resisting its working stroke >0.5 pN. Moreover, the rate of actin translocation in the in vitro motility assay is similar for both myo1b (21) and myo1c (16) (when corrected for the differences in length of the light chain-binding domain). Given the similarity of their unloaded biochemical properties, one may have expected myo1c to share the force-sensing properties of myo1b (22,23).…”
mentioning
confidence: 98%
“…The rate constants that define the myo1c actin-activated ATPase pathway in solution are very similar to myo1b (10,12,16,19), a closely related myosin-I isoform that has actin-detachment kinetics that are exquisitely sensitive to tension (20). Myo1b is suited to function as a tension-sensitive anchor, transforming from a low duty-ratio motor to a high duty ratio-motor with forces resisting its working stroke >0.5 pN.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Expression and purification of His-ZO1-PDZ1 protein have also been described previously (14,39). Recombinant proteins Flag-Myo1c-FL and GFP-HisMyo1c-tail were produced in a baculovirus expression system as described previously (40,41). Two peptides, ERTPYEAYDPIGKYATATRF and YE KFNSHPFPGAAGYPTYRL, derived from the K761 region of Neph1 and the region of Neph1 not involved in Myo1c binding, respectively, were synthesized chemically using standard 9-fluorenylmethoxy carbonyl (Fmoc) solid-phase chemistry, and 2-chloro trityl resin was used as a solid support (PTI peptide synthesizer).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, in vitro and cellular studies have shown that cargo docking by Myo1c is regulated by the presence of non-muscle tropomyosin, which might spatially regulate the location of cargo docking to tropomyosin-free filaments just beneath the plasma membrane (Kee et al, 2015;McIntosh et al, 2015). Myo1c has also been implicated in the mechanical adaptation of signaling in inner ear hair cells (Batters et al, 2004;Gillespie et al, 1993;Holt et al, 2002;Lin et al, 2011), as well as in the regulation of a Na + channel after antidiuretic hormone stimulation in the kidney collection ducts (Wagner et al, 2005). Myo1b has been proposed to tether amino acid transporters to the apical plasma membrane of kidney cells, thereby facilitating neutral amino acid transport across the membrane; however, more investigation is needed to differentiate this hypothesis from other potential roles, such as facilitating membrane fusion of vesicles containing amino acid transporters, and/or mediating the transport and/or sorting of these cargo to the apical plasma membrane (Komaba and Coluccio, 2015).…”
Section: Myosin-i Is a Molecular Dock Or Tethermentioning
confidence: 99%